Skeptouchoi in the Caucasus and the Northern Black Sea region in the ancient era - E. V. Vdovchenkov; A. P. Voskresenskiy (Кавказология)
Among the terms used by ancient authors for barbarian rulers is the term skeptouchoi. This article raises the problem of the content of this term to characterize the barbaric societies of the Northern Black Sea region and the Caucasus. Strabo reports on skeptouchoi in the Pre-Caucasus and skeptouchoi in Colchis. Skeptouchoi are known in Tacitus' description of the Sarmatian raid on Transcaucasia, they are also mentioned in the decree of the Protogenes of the second half of the III century BC – the beginning of the II century AD, which tells about the tributary relations of Olbia and the Sayy tribe. Of particular importance is the information of Strabo, where he speaks about two levels of power. The presence of such a form of political organization as chiefdom in these societies has been established. The article also analyzes the archaeological situation in the Northwestern Caucasus and Colchis. It is concluded that the ancient authors, speaking of skeptouchoi, meant regional rulers, often subordinate to rulers of a higher level – czars.